2014
DOI: 10.1179/2049396714y.0000000085
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to polycyclic aromatic hydrocarbons (PAHs) and bladder cancer: evaluation from a gene-environment perspective in a hospital-based case-control study in the Canary Islands (Spain)

Abstract: Background: Exposure to polycyclic aromatic hydrocarbons (PAHs) has been linked to bladder cancer. Objective: To evaluate the role of PAHs in bladder cancer, PAHs serum levels were measured in patients and controls from a case-control study. Methods: A total of 140 bladder cancer patients and 206 healthy controls were included in the study. Sixteen PAHs were analyzed from the serum of subjects by gas chromatography-mass spectrometry. Results: Serum PAHs did not appear to be related to bladder cancer risk, alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 46 publications
1
23
2
Order By: Relevance
“…Specific ratios of individual PAHs are characteristic for some combustion processes and many authors used diagnostic ratios of PAHs to identify potential pollution sources [ 10 , 11 , 12 , 13 ]. In this study, the following ratios were selected: IP/(IP + BghiP), BaP/BghiP, Flu/(Flu + Pyr), and BaP/(BaP + Chry).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific ratios of individual PAHs are characteristic for some combustion processes and many authors used diagnostic ratios of PAHs to identify potential pollution sources [ 10 , 11 , 12 , 13 ]. In this study, the following ratios were selected: IP/(IP + BghiP), BaP/BghiP, Flu/(Flu + Pyr), and BaP/(BaP + Chry).…”
Section: Resultsmentioning
confidence: 99%
“…Bladder cancer is also linked to exposure to PAHs. Boada et al [ 10 ] conducted a case study in the Canary Islands measuring PAH serum levels of 140 patients diagnosed for bladder cancer. Their results showed a difference in PAH contamination profile between patients and the control group, leading to the conclusion that specific PAH mixtures play a role in bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It is well documented that occupational exposure to chemical carcinogens including aromatic amines and polycyclic aromatic hydrocarbons is associated with the risk of bladder cancer development [2, 4]. Kellen et al reported an increased risk of developing bladder cancer associated with cumulative exposure to aromatic amines, but not to PAHs and diesel [5].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the efficiency of the PAHs in reaching to the tracheobronchial or alveolar region of the human respiratory tract and even to the bloodstream (Kajiwara et al, 2007;Monsalve et al, 2013;Velali et al, 2016) enhances as the substrate aerosol size decreases. The population-based cohort studies using a quantitative assessment of PAH exposure revealed intrauterine growth restriction inducing low birth weight (Choi et al, 2012;Polanska et al, 2014), fatal ischemic heart disease (Burstyn et al, 2005), enhanced risk of asthma in children (Al-Daghri et al, 2013;Karimi et al, 2015) and cancer in humans (Boada et al, 2015).…”
Section: Introductionmentioning
confidence: 99%